Functional characterization of a bovine luteal cell culture model: Effects of passage number - Arpna Sharma; Jens Vanselow; Christa Kühn; Doreen Becker (PLoS ONE, 2025)
Primary cell culture models are useful tools to analyze intracellular signaling pathways and interactions in detail. However, at higher passages, vital cell characteristics such as cell morphology, physiology, gene expression and cell proliferation can be compromised which may result in variable data. In the present study, we characterized cultured primary luteal cells (PLCs) and compared them to intermediate passaged luteal cells i.e. passage number 15 (P15) and high passaged luteal cells i.e. passage number 30 (P30). To explore in-vitro culture induced variabilities, PLCs were passaged repeatedly until passage number P30. Expression of cell cytoskeleton proteins was monitored by immunofluorescence and steroidogenic acute regulatory (STAR) protein expression was detected by capillary electrophoresis as physiological key parameter. The abundance of STAR, hydroxy-delta-5-steroid dehydrogenase, 3 beta- and steroid delta-isomerase 1 (HSD3B1) and luteinizing hormone/choriogonadotropin receptor (LHCGR) marker transcripts was quantified by RT-qPCR. Cell proliferation and cell viability of luteal cells were evaluated using flow cytometry. Global gene expression profiling by RNA sequencing was performed on early passaged (P3) luteal cells. Cell passaging severely reduced the expression of genes encoding marker proteins of luteal cells. Similarly, progesterone (P4) synthesis and cell proliferation were reduced significantly at higher passages. Early passaged (P3) luteal cells expressed key genes of luteal cells but with lower expression values. Luteal cells remained highly viable and consistently co-expressed both vimentin and cytokeratin-18 protein in their cytoskeleton irrespective of passage number. Together, these findings demonstrate that only short-term luteal cell primary cultures or very early passaged luteal cells (P3) are able to display molecular features that resemble that of the corpus luteum in vivo and thus are suitable in vitro models.